Managerial and Customer Costs of Price Adjustment: Direct Evidence from Industrial Markets - Mark J. Zbaracki; Mark Ritson; Daniel Levy; Shantanu Dutta; Mark Bergen (Review of Economics and Statistics, 2004)
We study the price adjustment practices and provide quantitative measurement of the managerial and customer costs of price adjustment using data from a large U.S. industrial manufacturer and its customers. We find that price adjustment costs are a much more complex construct than the existing industrial-organization or macroeconomics literature recognizes. In addition to physical costs (menu costs), we identify and measure three types of managerial costs (information gathering, decision-making, and communication costs) and two types of customer costs (communication and negotiation costs). We find that the managerial costs are more than 6 times, and customer costs are more than 20 times, the menu costs. In total, the price adjustment costs comprise 1.22% of the company's revenue and 20.03% of the company's net margin. We show that many components of the managerial and customer costs are convex, whereas the menu costs are not. We also document the link between price adjustment costs and price rigidity. Finally, we provide evidence of managers' fear of antagonizing customers.
Keywords: E12; E31; L16; F31; F41; 330; Menu Cost; Cost of Price Adjustment; Sticky Prices; Rigid Prices; Price Rigidity; Customer Antagonization Cost; Convex Costs of Price Adjustment; Customer Costs of Price Adjustment; Managerial Costs of Price Adjustment